Nilai-nilai Moral dalam Sastra Klasik Folklor “Legenda Curug Orok” di Desa Cikandang, Kecamatan Cikajang Kabupaten Garut sebagai Upaya Pelestarian Nilai Budaya - Iin Indriyani; Umi Kulsum (Institut Pendidikan Indonesia, 2021)
AbstractFairy tales are one of the cultural products originating from the Indonesian people. The spread of fairy tales in society is spread by word of mouth. The existence of fairy tales is almost extinct today, eroded by the sophistication of communication technology, even many young people today do not know that in the area where they live, there are stories stored. In fact, if we explore the contents of the messages in these fairy tales, there are a lot of moral values that can be used as guidelines for living life. Moral value is a value that regulates the way of life when we are in a society. The purpose of this study is to analyze the moral values in the folklore entitled